m6A-related genes of peripheral white blood cell in spinal cord injury as potential targets for prognosis and treatment - Luo, Mingran; Wang, Qian; Chen, Jian; Yin, Guoyong (Frontiers in Medicine, 2025)
ObjectiveSpinal cord injury (SCI) is a destructive neurological and pathological state that causes major motor, sensory, and autonomic dysfunction. N6-methyladenosine (m6A) is a reversible RNA modification implicated in various biological processes. However, few studies have examined m6A expression in patients with SCI. We explored the prognostic value of m6A-related genes as potential biomarkers in SCI to establish a set of accurate diagnostic and prognostic prediction models.MethodsDifferentially expressed analysis and weighted gene co-expression network analysis (WGCNA) was used to explore m6a related modules and hub genes. KEGG and GO analyses was utilized to explore the potential role of these hub genes. Gene expression was verified in single-cell data. The correlation of m6A related gene with spinal cord injury severity was explored.ResultsWe found 289 SCI-related and five m6A-related candidate genes with high SCI correlation and high differential expression in the publicly available dataset, GSE151371. These genes are also involved in long-chain fatty acid binding. Early SCI was accompanied by significant immune cell infiltration. Simultaneously, infiltrating immune cells and the innate immune system have a strong cellular interaction, which gradually decreases over time. The number of PPARG-positive cells also increases after SCI. The comparatively higher expression of PPARG and lower expression of AK5 in white blood cells (WBCs) correlates with severity of SCI.ConclusionOur integrated analysis illustrates the hub genes involved in SCI, which can be prognostic markers. Further understanding of the functions of the identified SCI hub genes may provide deeper insights into the molecular mechanisms of SCI.